Varnost v lokalnih skupnostih: II. zbornik raziskovalnega dela študentov Fakultete za varnostne vede Univerze v Mariboru - Pirnat, Urška; Meško, Gorazd; Eman, Katja (2019)
Safety and Security in Local Communities: 2nd Compilation of Research Papers Authored by the Students of the Faculty of Criminal Justice and Security, University of MariborThe present compilation of research papers is the second edition of peer-reviewed papers produced in the framework of the “Safety and Security in Local Communities” course, which is part of the Master’s Study Programme at the Faculty of Criminal Justice and Security, University of Maribor. The papers are the result of research work conducted by students in the spring of 2018. They were presented at the Second International Conference entitled “Safety and Security in Local Communities – Legal and Criminological Perspectives”, which was organised by the Montenegrin Faculty of Law in Podgorica in April 2018. In the framework of their course, students used databases of research conducted in 2011 and 2017 by the Programme Group on Safety and Security in Local Communities (2015–2018) to perform secondary data analyses and compare residents’ perceptions of safety and security in their local communities, as well as to examine relevant demographic factors.
Keywords: safety; security; local community; survey; students; Slovenia